DETERMINANT OF THE AUDITOR SWITCHING ON MANUFACTURING COMPANY IN INDONESIA STOCK EXCHANGE - Arfan Ikhsan; Esa Setiana; Syahrijal Hidayat; Yerisma Welly (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2022)
Research aims to test the effet of Audit Opinion (AO), Financial Distress (FD), and Corporate Growth (CG) on Auditors Switching (AS) at Manufacturing Companies. Research population is manufacturing company registered on the BEI in 2016-2020. From 192 listed companies, 43 companies were chosen as samples based on established criteria by using purposive sampling method. The data used in this research is secondary data get from the company in annual report. Method of data analysis used is logistic regression. The results showed that: 1) audit opinion variables affect the AS. 2) FD has no effect on the auditor switching. 3). GC has no effect on the AS. The conclusion research is AO able to determine company to do AS. While FD and CG have no influence to the company to do auditor switching. Keywords: Auditor Switching, Audit Opinion, Financial Distress, Corporate Growth.